2021
DOI: 10.26803/ijlter.20.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Implementing Problem-Based Language Learning: Experiences from a Seven-Year Journey

Abstract: The purpose of this paper is twofold. First, it aims to identify the challenges and barriers experienced in implementing problem-based Learning (PBL) in a language program at Sultan Qaboos University in the Sultanate of Oman. Second, it proposes a working model for integrating PBL into an existing program. The research was conducted using a case study approach underpinned by design-based research principles. The proposed model came as a result of tracing the development of the program over a period of seven ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Problem-based Learning is a model based on using problems as a starting point for the acquisition and integration of new knowledge. With this learning, students are introduced from the start to various life problems that they may encounter later when they graduate from school [12,58]. However, adopting problem-based Learning into Learning faces challenges because of several factors, including belief factors and problems with learning practices carried out by teachers [89].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Problem-based Learning is a model based on using problems as a starting point for the acquisition and integration of new knowledge. With this learning, students are introduced from the start to various life problems that they may encounter later when they graduate from school [12,58]. However, adopting problem-based Learning into Learning faces challenges because of several factors, including belief factors and problems with learning practices carried out by teachers [89].…”
Section: Discussionmentioning
confidence: 99%
“…states that Problem-based Learning combines cognitive theory and constructivism to develop cognitive processes by providing opportunities to learn in relevant situations. Problem-based Learning is also expressed as a form of realization of constructivism with students actively involved in learning through cognitive processes and interactions with the environment [8,58]. [59] states that problem-based learning syntax consists of five main phases described in the following table.…”
Section: Problem-based Learningmentioning
confidence: 99%
“…According to Moh'd et al (2015), when instructors fail to actively involve students in class discussions, students tend to apply rote learning, which hinders them from acquiring critical thinking skills. Al-Busaidi, Yusuf and Reinders (2021) reported that research has also established collaboration, which promotes a deep learning approach can be achieved in the classroom through the introduction of problem-based learning. Tee-Meng ( 2016) has suggested that some of the techniques instructors could adopt in order to assist students imbibe deep learning approaches include role playing, and small and large group discussions.…”
Section: Discussionmentioning
confidence: 99%
“…Fan (2019) suggested that course curriculum should be practice-oriented to produce students to meet the needs and expectations of the workplace and employers, satisfying requirements for industry development. Al-Busaidi et al (2021) believe that PBL emphasises the meaningful use of language as a tool for communication and problem-solving.…”
Section: Problem-based Learningmentioning
confidence: 99%
“…The implementation steps and key points of PBL have been in place for many years, and there are various versions and approaches, but the core concepts and aims are the same (Al-Busaidi et al, 2021). According to Barrett & Moore (2011) and Flipped Education and Action Learning Association (2018), PBL can be divided into the following seven stages: 1. problem-solving; 2. case-based; 3. selfdirected; 4. small group discussion; 5. tutor-assisted; 6. self-assessment; 7. development of interpersonal skills.…”
Section: Problem-based Learningmentioning
confidence: 99%